Co-Production in Innovation Development: A Case Study of the Republik Melon in Wates District, Blitar Regency: Co-Production dalam Pengembangan Inovasi: Studi Kasus Republik Melon di Kecamatan Wates Kabupaten Blitar - Nurul Nurhidayati; Bagus Nuari Harmawan (Universitas Indo Global Mandiri, 2026)
Purpose : This research aims to identify the forms of melon farmers’ involvement and the social changes experienced by farmers in the Republik Melon program through a co-production approach. Design/methodology/approach : This study was conducted within the Republik Melon innovation program in Wates District, Blitar Regency, using a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation to explore program implementation and stakeholder involvement. Findings : The findings show that melon farmers are actively involved in the development of the Republik Melon program and directly benefit from its implementation. The program contributes to economic improvement and social welfare, particularly through the creation of new employment opportunities for farmers. In addition to melon farmers, the program involves cross-sector collaboration with several actors, including the Blitar Regency Office of Food Security and Agriculture (DKPP), Bappedalitbang of Blitar Regency, the Wates District Government, the Wates Agricultural Extension Center (BPP), the Wates Women Farmers Group, and MSMEs in Tugurejo Village. Practical Implication : The results can be used by local governments and program implementers as evaluation material and a basis for decision-making to improve the effectiveness and sustainability of the Republik Melon program. The co-production approach may also serve as a reference for strengthening collaboration and community participation in other regional innovation programs. Originality/value : This study highlights a greenhouse-based agricultural innovation that positions farmers as key actors, reflecting the principles of co-production and the values of collaboration, empowerment, and community participation in modern public administration.